2020
DOI: 10.1149/1945-7111/ab717f
|View full text |Cite
|
Sign up to set email alerts
|

3D Carbon Nanotubes Spaced Graphene Aerogel Incorporated with Prussian Blue Nanoparticles for Real-Time Detection of H2O2 Released from Living Cells

Abstract: Real-time detection of hydrogen peroxide (H2O2) released from living cells is of great value in further understanding the occurrence process of some diseases and searching for new therapeutic strategies. However, selective monitoring of H2O2 in living cells is still a huge challenge due to its low concentration, large diffusivity and high reactivity. Herein, three-dimensional carbon nanotubes spaced graphene aerogel incorporated with Prussian blue nanoparticles (3D PB NPs/G-CNTs) has been successfully synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
2
3
1
Order By: Relevance
“…It is reported H 2 O 2 can be fast released from living cells upon the stimulation of PMA. The monitored current response by PMA stimulation was 1.05 μA, which corresponded to 13.32 μM H 2 O 2 according to the calibration curve in Figure b, and equaled 0.053 fmol released H 2 O 2 per cell, which is in good agreement with the previous report. , This also further confirms the high sensitivity of this sensor even as low as 0.05 fmol molecules.…”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is reported H 2 O 2 can be fast released from living cells upon the stimulation of PMA. The monitored current response by PMA stimulation was 1.05 μA, which corresponded to 13.32 μM H 2 O 2 according to the calibration curve in Figure b, and equaled 0.053 fmol released H 2 O 2 per cell, which is in good agreement with the previous report. , This also further confirms the high sensitivity of this sensor even as low as 0.05 fmol molecules.…”
Section: Results and Discussionsupporting
confidence: 91%
“…In more detail, after injection of PMA (600 ng/mL) in 4 mL of PBS containing 1 × 10 6 of A549 living cells to stimulate H 2 O 2 release, instant current response was observed as shown in curve a (Figure 5d), while control experiments showed that no 5b, and equaled 0.053 fmol released H 2 O 2 per cell, which is in good agreement with the previous report. 24,25 This also further confirms the high sensitivity of this sensor even as low as 0.05 fmol molecules. Iron single atomic site catalyst dispersed on 1-D carbon nanowires (Fe-SASC/NW) as a nanozyme has been reported to sensing H 2 O 2 but only showing a sensitivity of 6.5 μA mM −1 cm 2 .…”
Section: Resultssupporting
confidence: 74%
“…[17] An intriguing application of the nanoparticle-loaded GO composites is their use as enzyme mimetics, perticularly for peroxidase mimicking. Various studies have investigated the peroxidase mimicking activity of Cu ions, [18,19] Ag/rGO nanocomposites, [20] 3D PB NPs/G-CNTs, [21] 3D PB/GMA (Prussian blue-doped RGO/MXene composite aerogel) [22] nitrogen-doped GO quantum dots, [23] GOÀ Fe 2 O 3 hybrids, [15] MoS 2 /GO hybrid, [24] polystyrene sulfonate/Pt/graphene nanosheets [17] for colorimetric detection of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GA shows excellent structural stability, which can tolerate the damage during the electrochemical reaction. Apart from the properties, the GA offers excellent potential in applying electrochemical sensors. However, there is no previous literature of YVO/GA nanocomposite being applied in the electrochemical sensor. In this spirit, YVO/GA nanocomposite was prepared through a sonochemical method and used as an electrode material toward the detection of DA.…”
Section: Introductionmentioning
confidence: 99%